Visual Perceptual Load Attenuates Age-Related Audiovisual Integration in an Audiovisual Discrimination Task - Ren, Yanna; Li, Hannan; Li, Yan; Wang, Tao; Yang, Weiping (Frontiers in Psychology, 2021)
Previous studies confirmed that the cognitive resources are limited for each person, and perceptual load affects the detection of stimulus greatly, however, how the visual perceptual load influences audiovisual integration (AVI) is still unclear. Here, twenty older and 20 younger adults were recruited to perform an auditory/visual discrimination task under various visual perceptual-load conditions. The analysis for the response times revealed a significantly faster response to the audiovisual stimulus than to the visual stimulus or auditory stimulus (all p < 0.001), and a significantly slower response by the older adults than by the younger adults to all targets (all p ≤ 0.024). The race-model analysis revealed a higher AV facilitation effect for older (12.54%) than for younger (7.08%) adults under low visual perceptual-load conditions; however, no obvious difference was found between younger (2.92%) and older (3.06%) adults under medium visual perceptual-load conditions. Only the AV depression effect was found for both younger and older adults under high visual perceptual-load conditions. Additionally, the peak latencies of AVI were significantly delayed in older adults under all visual perceptual-load conditions. These results suggested that visual perceptual load decreased AVI (i.e. depression effects), and the AVI effect was increased but delayed for older adults.